The Implementation of the 2013 Curriculum in English Language Teaching - Ludovikus Ludovikus; Yuyun Yulia (Universitas Sarjanawiyata Tamansiswa, 2021)
This study is aimed at (1) describing the 2013 Curriculum implementation in the ELT process and (2) investigating the strengths and weaknesses of online learning. The researcher selected English language teaching at SMP Joannes Bosco Yogyakarta as a research site, especially for both a senior English teacher and seventh-grade students as the participants. The researcher used a case study. The case of this research was the teaching-learning process and the students’ problems at SMP Joannes Bosco Yogyakarta in learning English. The data used were recorded observation (teaching and learning process), document (lesson plan, syllabus, and curriculum), interview (the senior English teacher about the way of teaching) and questionnaires (for 7th-grade students about their difficulties). The collected data in this research were analyzed descriptively. Based on the data analysis, findings show that the teacher did not apply the scientific approach (observing, questioning, experimenting, associating, communicating) effectively or optimally. The strengths and weaknesses of online learning were various. The strengths were such as the process of ELT, media use, and students’ task or activity. The weaknesses were such as the teaching and learning were boring, students had no good internet connection, students could not concentrate very well, nobody accompanied them at home, and students got bored easily.